2015
DOI: 10.1002/ece3.1383
|View full text |Cite
|
Sign up to set email alerts
|

On the use of stable oxygen isotope (δ18O) measurements for tracking avian movements in North America

Abstract: Tracking migratory animals has benefitted using measurements of naturally occurring stable isotopes of hydrogen (δ2H) in keratinous tissues such as hair and feathers to link animal origins to continental patterns or isoscapes of δ2H in precipitation. However, for most taxa, much less information exists on the use of stable oxygen isotope ratios (δ18O) despite the fact that δ2H and δ18O are strongly linked in environmental waters through the meteoric relationship and the possibility of using both isotopes to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 38 publications
3
37
0
Order By: Relevance
“…Modeling suggested that these distinctive values could be explained by the expected preferential atomic routing of H from 2 H-enriched marine dietary items to keratin combined with the dominance of 18 O-depleted drinking water on keratin 18 O. This suggests that the dual-isotope system (Hobson et al, 2004;Myers et al, 2012;Hobson and Koehler, 2015). Some potential contributors to the relatively poor relationship in δ 18 O values may be due to the exchanges of O in body water with O in the CO 2 of dissolved body water (McCluney and Sabo, 2010), or that in aquatic organisms, organically bound oxygen, particularly Ehleringer et al, 2008) and Asian cities (n = 25, Thompson et al, 2010) as well as mid-twentieth century indigenous populations (n = 26, Bowen et al, 2009).…”
Section: Decoupling In Tissue and Environmental Watermentioning
confidence: 99%
“…Modeling suggested that these distinctive values could be explained by the expected preferential atomic routing of H from 2 H-enriched marine dietary items to keratin combined with the dominance of 18 O-depleted drinking water on keratin 18 O. This suggests that the dual-isotope system (Hobson et al, 2004;Myers et al, 2012;Hobson and Koehler, 2015). Some potential contributors to the relatively poor relationship in δ 18 O values may be due to the exchanges of O in body water with O in the CO 2 of dissolved body water (McCluney and Sabo, 2010), or that in aquatic organisms, organically bound oxygen, particularly Ehleringer et al, 2008) and Asian cities (n = 25, Thompson et al, 2010) as well as mid-twentieth century indigenous populations (n = 26, Bowen et al, 2009).…”
Section: Decoupling In Tissue and Environmental Watermentioning
confidence: 99%
“…Although the δ 18 O bodywater of modern birds has not been reported extensively, Kerstel et al . () reported that stable oxygen isotopes in the body water of shorebirds occur at ‘natural abundances’ while Hobson & Koehler () suggested a close association between δ 18 O bodywater and meteoric water ingested by migrating terrestrial birds. Schaffner & Swart () reported that ingested water is the only source of δ 18 O bodywater in terrestrial vertebrates including birds, with only minor short term fluctuations due to respiration and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…). Although there is no exchange of oxygen with ambient water vapour during respiration in birds (Hobson & Koehler ), Amiot et al . () noted an enrichment of δ 18 O bodywater in semiaquatic crocodiles, which are distantly related to birds (archosaurs) and also use evaporative cooling, of up to 2‰.…”
Section: Discussionmentioning
confidence: 99%
“…For provenance assignment in ecology, δ 2 H has been the most commonly used isotope marker, largely due to analytical accessibility. δ 18 O has been less commonly used due to analytical difficulties, especially with small samples (discussed below), plus assignment of provenance is potentially complicated due to animals sourcing O from air as well as water and food . However, provenance resolution can be improved by considering δ 2 H and δ 18 O together, as they serve as semi‐independent markers due to differences in evaporative response .…”
Section: Introductionmentioning
confidence: 99%
“…18 O has been less commonly used due to analytical difficulties, 27 especially with small samples (discussed below), plus assignment of provenance is potentially complicated due to animals sourcing O from air as well as water and food. 28 However, provenance resolution can be improved by considering 2 H and 18 O together, as they serve as semi-independent markers due to differences in evaporative response. 27,29,30 Additionally and importantly, data derived from separate isotope systems also permits the use of more powerful, multivariate statistical analyses.…”
Section: Introductionmentioning
confidence: 99%